Aqueous Solubility and Bioavailability of Albumin Conjugated Curcumin in Endothelial Cells Allege Potential of the Formulation for Anti-Inflammation Therapy - Sathee, Deepa; Krishnan, Lissy Kalliyana (Cardiology and Cardiovascular Medicine, 2021)
Endothelial cell (EC) activation and chronic inflammation can cause the initiation and progression of atherosclerosis. Curcumin (CM) is a potential candidate drug with minimal side effects. However, poor aqueous solubility, lack of bioavailability, and high hydrolytic degradation are limiting its clinical use. Conjugation of CM to Albumin (Alb) producing CM-Alb increases the solubility of the potential drug. This study evaluates an albumin-CM conjugate for cellular uptake demonstrating bioavailability, determining the non-cytotoxic concentrations and anti-inflammatory response in human umbilical vein endothelial cells (HUVECs). The maximum tolerated biocompatible dose determined in HUVEC (EC) culture is 30μM; accordingly, this study evaluates an anti-inflammatory response at non-toxic concentrations. The experiments using fluorescence microscopy and flow cytometry confirmed the endocytosis of fluorescent-tagged CM-Alb and showed comparable cellular uptake of native albumin. Cytokine- induced activation of inflammation in EC culture was standardized as in vitro model for evaluating the response to CM-Alb. Using quantitative real-time polymerase chain reaction (RT-PCR), the established upregulation of inflammatory markers in EC cultures stimulated with TNF-α proposes it as a suitable culture model to study the anti-inflammatory response of CM-Alb. Inflammatory markers were down- regulated by the non-cytotoxicconcentration (<30 μM) of CM-Alb on adding into cytokine-activated ECs. Expressions of markers at a protein level in cytokine-activated EC drop down to normalcy when treated with CM-Alb. In conclusion, increased aqueous solubility and receptormediated uptake of CM- Alb conjugate by ECs caused an anti-inflammatory response in the inflammation-induced culture model, advocating the potential for further study as an intravenous therapeutic formulation.